2014
DOI: 10.1590/1519-6984.00113
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Drosophilidae (Diptera) assemblages from two highland Araucaria Forest fragments, with and without environmental conservation policies

Abstract: Flies from the Drosophilidae family are model organisms for biological studies and are often suggested as bioindicators of environmental quality. The Araucaria Forest, one of Atlantic Forest phyto-physiognomy, displays a highly fragmented distribution due to the expansion of agriculture and urbanization. Thus, this work aimed to evaluate and compare the drosophilid assemblages from two highland Araucaria Forest fragments, one a conservation unit (PMA -Parque Municipal das Araucárias) and the other a private pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 27 publications
0
9
0
3
Order By: Relevance
“…The oriental species D. kikkawai supports a cosmopolitan status (Pinheiro and Valente, 1993), but it is not clear when it was introduced in South America and Africa and nor if this process was mediated by humans (Ashburner, 1989). In Brazil, this species is found in both natural (Sene et al, 1980) and urban environments (Costa et al, 2003), usually in low abundances (but see Cavasini et al, 2014).…”
Section: Subgenus Sophophora Sturtevantmentioning
confidence: 99%
See 1 more Smart Citation
“…The oriental species D. kikkawai supports a cosmopolitan status (Pinheiro and Valente, 1993), but it is not clear when it was introduced in South America and Africa and nor if this process was mediated by humans (Ashburner, 1989). In Brazil, this species is found in both natural (Sene et al, 1980) and urban environments (Costa et al, 2003), usually in low abundances (but see Cavasini et al, 2014).…”
Section: Subgenus Sophophora Sturtevantmentioning
confidence: 99%
“…In Brazil, drosophilid communities have been studied by several independent research groups, covering the Amazonian and Atlantic forests (Medeiros and Klaczko, 2004;Penariol and Madi-Ravazzi, 2013;Coutinho-Silva et al, 2017;Santa-Brígida et al, 2017), the Cerrado biome (Tidon, 2006;Blauth and Gottschalk, 2007), Caatinga (Rohde et al, 2010;Garcia et al, 2014;Oliveira et al, 2016), araucarias (Cavasini et al, 2014), pampas (Poppe et al, 2016) and urban sites (Ferreira and Tidon, 2005;Gottschalk et al, 2007). Exotic species are recorded in all drosophilid assemblages, and their relative abundance depends on many factors, as vegetation type, the season of the year, and disturbance (Mata et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Cavasini et al (2014) evaluated the Drosophilidae assemblages of Araucaria Forest fragments in Guarapuava/PR (southern of Brazil), including one studied here. They concluded that the areas are in intermediate state of conservation, and the size of the preserved area and/or connection with other fragments are important and should be considered for the establishment of conservation units.…”
Section: Migration Rate and Genetic Diversity Of Twomentioning
confidence: 99%
“…Drosophila griseolineata Duda, 1927 Substratos de desenvolvimento larval (Duda, 1927;Dobzhansky & Pavan, 1943;Dobzhansky & Cunha, 1955;Hunter, 1964;Hunter, 1970;Brncic & Valente, 1978;Sene et al, 1980;Rafael & Vela, 2000;Roque et al, 2013;Cavasini et al, 2014). Duda, 1927 Substratos Tidon-Sklorz et al, 1994;De Toni & Hofmann, 1995;Tidon-Sklorz & Sene, 1995;Goñi et al, 1998;Leão & Tidon, 2004;Mateus et al, 2006;Martins & Oliveira, 2007;Mata et al, 2008;Acurio & Rafael, 2009;Tidon & Almeida, 2006).…”
Section: Grupo Guaranimentioning
confidence: 99%
“…Substratos de desenvolvimento larval Literatura: Desconhecidos. Gottschalk et al, 2007;Hochmuller et al, 2010;Cavasini et al, 2014).…”
Section: Drosophila Platitarsus Frota-pessoa 1954unclassified